Urine Tenofovir Concentrations Correlate With Plasma and Relate to Tenofovir Disoproxil Fumarate Adherence: A Randomized, Directly Observed Pharmacokinetic Trial (TARGET Study). (17th July 2019) - Drain, Paul K; Kubiak, Rachel W; Siriprakaisil, Oraphan; Klinbuayaem, Virat; Quame-Amaglo, Justice; Sukrakanchana, Pra-Ornsuda; Tanasri, Suriyan; Punyati, Pimpinun; Sirirungsi, Wasna; Cressey, Ratchada; Bacchetti, Peter; Okochi, Hideaki; et al.
Abstract: Background: Direct measurement of tenofovir (TFV) in urine could be an objective measure to monitor adherence to preexposure prophylaxis (PrEP) or TFV-based antiretroviral therapy (ART). Methods: We conducted a 3-arm randomized, pharmacokinetic study of tenofovir disoproxil fumarate (TDF) 300 mg/emtricitabine (FTC) 200 mg among adults living with human immunodeficiency virus. Participants were randomized to receive controlled TDF/FTC dosing as (1) "perfect" adherence (daily); (2) "moderate" adherence (4 doses/week); or (3) "low" adherence (2 doses/week). We obtained trough spot urine and plasma samples during a 6-week directly observed therapy period and a 4-week washout period. TFV concentrations were compared between adherence arms using 1-way analysis of variance. Results: Among 28 participants, the median age was 33 years and 16 (57%) were male. Correlation between TFV plasma and urine concentrations was strong (ρ = 0.78; P < .0001). Median (interquartile range) steady-state trough TFV concentrations (ng/mL) for perfect, moderate, and low TDF adherence were 41 (26–52), 16 (14–19), and 4 (3–5) in plasma; and 6480 (3940–14 300), 3405 (2210–5020), and 448 (228–675) in urine. Trough TFV concentrations at steady state were significantly different between the 3 adherence arms for plasma ( P < .0001) and urine ( P = .0002). Following drug cessation, TFV concentrations persisted longer in urine than plasma samples. Washout urine TFV concentrations and time to undetectable concentrations did not differ between the 3 randomized adherence groups. Conclusions: Urine TFV concentrations can inform interpretation of novel point-of-care urine-based TFV assays to assess recent TDF adherence. Clinical Trials Registration: NCT0301260. Abstract : Measurement of tenofovir directly in urine would be a novel tool to monitor adherence to preexposure prophylaxis or tenofovir-based antiretroviral therapy. Urine concentrations of tenofovir are related to recent adherence of tenofovir disoproxil fumarate in adults.